EFFECT MNB SUPPLEMENTATION ON THE GRASS FIELD OF BASIC FEED PERFORMANCE AND CARCASS LOCAL MALE RABBIT (Lepus nigricollis) - I. G. P. E., KUSUMA,; DEWI, G. A. M KRISTINA; NURIYASA, I M. (Majalah Ilmiah Peternakan, 2017)
The research of the performance and carcass local male rabbit result mineral nutrient block (MNB)supplementation on ration-based grass field carried in Dajan Peken Village, Tabanan Regency (50 masl) formaintenance and cuts that lasted for 3 months. The design used in this research is a randomized block design, withfive replications. The rabbits were allocated randomly into four treatments, namely rabbits treated control rationis grass field (R0), control ration supplemented MNB 15 g/head/day (R1), control ration supplemented MNB 30 g/head/day (R2), control ration supplemented MNB 45 g/head/day (R3). Rations and drinking water given ad_libitum.Based on the results that the variable performance and carcass local male rabbits given MNB-supplemented rationswith 45 g/head/day (R3) showed a higher yield than R0 ration treatment (control) and other treatments.